Continuance intention of mobile commerce usage activities: Does personal innovativeness matter? - Azyanee Luqman; Razli Che Razak; Mohammad Ismail; Mohd Afifie Mohd Alwi (Medwell Journals, 2016)
This research aims to examine Malaysian consumers’ mobile commerce continuance intention by integrating the Expectation-Confirmation Model (ECM) with personal innovativeness. Data was collected from 122 consumers who had prior experience using mobile commerce activities and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. Findings revealed that satisfaction and personal innovativeness were found to be significantly related to continuance intention, explaining 36% of the variance. Surprisingly, perceived usefulness was found to have no significant relationship with continuance intention. Finally, limitations, recommendations for future research and implications of the study are also elaborated.